The factors controlling along-arc and across-arc variations of primitive arc magma compositions: A global perspective - Wang, Jian; Gleeson, Matthew; Smith, William D.; Ma, Lin; Lei, Zhibin; Shi, Guanghai; Chen, Long (Frontiers in Earth Science, 2022)
Arc volcanism is a key process influencing Earth’s climate, continental growth, and the formation of mineral deposits. Therefore in this contribution, we have compiled whole-rock geochemistry of frontal arc and rear-/back-arc basalts, crustal thickness, and slab parameters (e.g. slab age, slab dip, convergence velocity) from global convergent margins to investigate the factors controlling along-arc and across-arc variations. Crustal thickness or lithosphere thickness plays a dominant role in elements immobile in aqueous fluids (e.g., Zr/Yb and Nb/Yb). The effect is imposed through mantle partial melting for both frontal arc and rear-/back-arc rocks. Slab thermal structure also affects these immobile elements and gives rise to along-arc variations. Both slab sediment and altered oceanic crust can melt especially in hot subduction zones which yield across-arc variations (e.g., Nd isotope). Aqueous fluids (represented by element ratios such as Ba/Nb and Sr/Nd) also show across-arc variations as they decrease toward rear-/back-arc. This meanwhile decreases mantle wedge melting as rear-/back-arcs show higher Zr/Yb and Nb/Yb. However, no correlations between aqueous fluids and slab parameters suggest aqueous fluids in arc rocks are controlled by complex processes. We summarize factors such as slab alteration, slab dehydration, and mantle metasomatism might impose an effect on the content of fluid mobile elements in arc rocks.